Pengaruh Variasi Densitas Ethylene Vinyl Acetate (EVA) terhadap Kenyamanan Plantar Pressure Pemain Basket - Dadang Mubin; Galih Farhanto; Edi Irwanto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the effect of varying Ethylene Vinyl Acetate (EVA) density in basketball shoe midsoles on plantar pressure distribution and subjective comfort. Using a repeated measures design with 20 basketball players, three EVA density variations were tested: low (0.15 g/cm³), medium (0.25 g/cm³), and high (0.35 g/cm³). Plantar pressure data were collected using in-shoe sensors during vertical landing, cutting, and sprinting maneuvers. The results indicated that medium-density EVA provided the most even pressure distribution (205 ±pm 10 kPa at the heel) compared to low density, which caused lateral instability, or high density, which drastically increased peak pressure (245 ±pm 15 kPa). ANOVA analysis confirmed a significant influence of density on foot kinetic variables (p < 0.001). In conclusion, an EVA density of 0.25 g/cm³ is the optimal point for balancing shock absorption and responsive stability to mitigate the risk of injuries such as plantar fasciitis.